Granite stone subjected to ultrasonic fatigue tests under three point bending modality (Fracture and Structural Integrity, 2019)
Ultrasonic fatigue tests are carried out under the modality of three points bending on the granite stone. The testing specimens present a prismatic shape with the dimensions: 12 x 3 x 0.8 centimeters, in order to be supported at the two ends (1 centimeter of support each side), and to configure the three points bending modality. Granite specimens are supported on an acrylic structure destined to fix and immobilize the specimens. Vibrating load is applied at the center of testing specimens by a self-designed and fabricated aluminum alloy awl, which dimensions have been obtained by modal numerical analysis to fit the resonance condition, necessary for the ultrasonic fatigue tests.Experimental results are obtained at room temperature and humidity comprised between 60 and 75%. The fatigue endurance is determined on this material under this modality of loading, and the fracture surfaces are analyzed to identify the principal trends related to crack initiation and propagation on this material.
Keywords: Granite stone; Three point bending; Ultrasonic loading; Fatigue endurance; Fracture surfaces